PECULIARITIES OF CLINICAL AND PARACLINICAL INVESTIGATIONS OF WOMEN WITH OVARIAN ENDOMETRIOMAS IN COMBINATION WITH PELVIC INFLAMMATORY DISEASE - Bihun, R.V.; Orishchak, I.K.; Henyk, N.I.; Ostrovska, O.M.; Vorobiy, V.D.; Zhukuliak, O.M. (World of Medicine and Biology, 2022)
Endometriomas occupy a significant part in the structure of genital endometriosis. A clinical and paraclinical study of 210 patients with endometriomas was conducted. 57 patients (27.1 %) had newly detected endometrial cysts ≤ 4 cm, 46 women (21.9 %) had cysts > 4 cm. Recurrent endometriomas ≤ 4 cm were detected in 71 patients (33.8 %), while > 4 cm were in 36 women (17.1 %). A higher age, severe pelvic pain, and severe manifestations of external genital endometriosis were found in patients with recurrent endometriomas compared to those with newly detected endometrial cysts. In young women, unilateral endometriomas up to 4 cm in size are more often combined with a mild form of genital endometriosis, whereas in older patients endometrioid ovarian cysts, regardless of size, recur more often, are combined with severe manifestations of genital endometriosis, and are accompanied by impaired reproductive function.